2020
DOI: 10.1002/hon.2741
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and survival outcomes of patients with primary cardiac lymphoma: A SEER‐based analysis

Abstract: This study aimed to evaluate the incidence and prognosis of primary cardiac lymphoma (PCL) by using the Surveillance, Epidemiology, and End Results Program (SEER) database. Patients diagnosed with PCL and the disease incidence in the SEER database from 1975 to 2016 were included. Overall survival (OS) and cause-specific survival (CSS) curves were calculated using the Kaplan-Meier method and compared by the log-rank test. Univariate and multivariable Cox proportional hazard regression analyses were used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Based on the maximum χ 2 and minimum P value in the X-tile software (18), the optimal cut-off value for age in PMCTs patients was objectively identified as 44 and 76 in the current study, which is considered to be more credible and accurate. In previous studies on PMCTs patients, age at diagnosis showed a strong prognostic association with OS (4,19). In our study, older age was found to be associated with higher odds of early mortality, with patients over 76-year old having the highest odds of early mortality, followed by the 44-76 age group and 44, which was similar to the optical age cut-off value for OS for PMCT patients (4).…”
Section: Discussionsupporting
confidence: 84%
“…Based on the maximum χ 2 and minimum P value in the X-tile software (18), the optimal cut-off value for age in PMCTs patients was objectively identified as 44 and 76 in the current study, which is considered to be more credible and accurate. In previous studies on PMCTs patients, age at diagnosis showed a strong prognostic association with OS (4,19). In our study, older age was found to be associated with higher odds of early mortality, with patients over 76-year old having the highest odds of early mortality, followed by the 44-76 age group and 44, which was similar to the optical age cut-off value for OS for PMCT patients (4).…”
Section: Discussionsupporting
confidence: 84%
“…According to the Surveillance, Epidemiology and End Results Program database between 1973 and 2015 [11] , in a total of 144 patients with PCL, more than 70% received chemotherapy. The 5-year overall survival and cause-specific survival rates were 36.1% and 47.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ann Arbor staging and Primary site were also significantly associated with DLBCL prognosis ( 22 ). As a long-term widely used clinical staging method for NHL, Ann Arbor staging was easily got and accessible, and its predictive efficacy was comparable to that of the Lugano staging in prognostic estimation ( 23 ), so it was reasonable to use Ann Arbor staging as a predictor in this study.…”
Section: Discussionmentioning
confidence: 99%